FUNCTIONALIZATION OF CORRUPTION ERADICATION COMMISSION (KPK) INVESTIGATIONS IN HANDLING CORRUPTION CRIMINAL ACTS AFTER THE NEW CRIMINAL CODE - Bekti, Rossa Purbo; Nuraeny, Henny (Al-Mubin, 2025)
The regulation of the National Criminal Code is in the public spotlight. One of them was because a number of articles in the new Criminal Code actually reduce the punishment for corruptors. The aim of this research was to analyze the handling of criminal acts of corruption at the KPK regarding changes to criminal acts of corruption in the Criminal Code. This research was a normative legal approach with an explanatory descriptive method to collect data in the field related. The Result show that The New Criminal Code, namely Law Number 1 of 2023, brings significant changes in handling corruption crimes, including in the context of the authority of the Corruption Eradication Commission (KPK). One of the main changes is that corruption is no longer considered an "extraordinary crime" but rather a general crime, which has an impact on the authority of the KPK. This change can limit the KPK's authority in handling corruption cases, especially related to wiretapping and handling crimes involving BUMN, where state losses are not necessarily considered a crime